Agriculture Finance Note One : Lessons Learned from World Bank Projects Using Matching Grants - Varangis, Panos (World Bank, Washington, DC, 2017)
This note aims at analyzing lessons learned from matching grants projects for farmers and agricultural SMEs and providing guidance to TTLs on successful design. It is part of a series of agriculture finance policy notes. This note has benefited from peer review comments by Mike Goldberg, Diane Hristova, and Simon Bell.